Should public hospitals be allowed to sell prenatal screening? A qualitative analysis of public consultation documents - Fystro, Joar (Nordisk Tidsskrift for Helseforskning, 2026)
In November 2023, the Norwegian government presented a proposal for public consultation suggesting that pregnant women without an indication for prenatal diagnostics should nonetheless be able to undergo non-invasiv prenatal testing (NIPT) at public hospitals, provided they themselves pay the market price for the test. The aim of this study was to investigate the arguments and the justifications that were used in the public consultation. The qualitative analysis reveals how the authorities emphasised practical-empirical arguments, asserting that the proposal would lead to more equal access to NIPT across the country and help retain health professionals in public service, while the stakeholders pointed out the principled implications of the proposal. Whether the government had failed to consider the potential ramifications of allowing private market logic within public hospital settings, or if it presented the proposal as a trail balloon for introducing similar schemes, remains unclear. Another possibility is that it believed NIPT to be distinct from other health services, and therefore the proposal would not set a precedent for similar payment schemes.
Keywords: bioethics; health policy; prenatal screening; privatization; public hospitals; qualitative research